FROM HORSES TO HUMANS : The Untold Story of Rotavirus in Sarawak - Tan, Cheng Siang (UNIMAS Publisher, 2025)
Rotavirus is one of the leading causes of severe diarrhoea worldwide, particularly affecting young children and the elderly. Before vaccines were introduced, the virus caused millions of hospitalisations and hundreds of thousands of death each year. Since the mid-2000s, vaccines have saved countless lives by providing strong protection against the most common strains.